Síntese e caracterização de β-dicetonas 4,4,4-tricloro-1-aril-1,3-butanodionas e seus respectivos β-dicetonatos de cobre e ferro - Martins, Mauro Janner (2009)
The present dissertation describe, initially, the synthesis of a new series of 4,4,4-trichloro-1-aryl-1,3-butanediones (3a-l) [Cl3CCOCHRCOR1], where R=H, CH3 and R1 = Ph, 4-CH3Ph, 3-OCH3Ph, 4-OCH3Ph, 4-FPh, 4-ClPh, 4- BrPh, 4-4 Bifenyl, 4-NO2Ph, 1-naftyl e 2-naftyl, from the hydrolysis reaction of the b-alcoxivinil trichloromethyl ketones, obtained through the acylation of acetals with trichloroacetyl chloride. This method which represent the most effective form of obtainment of the compounds chloride dicarbonylic. The series of the compounds was obtained with great yields between 76-92%. The structures of compounds were determined by 1H NMR and 13C NMR spectroscopy, CG-MS and infra red analyses and, in some cases, X-rays diffraction. From the data obtained in the X-ray diffraction, was realized a structural study of diketones. This data furnished important informations about bond length, bond and dihedral angles in the crystalline form of compounds. Furthermore, the experimental crystallographic data were compared with data obtained from semi-empirical AM1calculations. Finally, were described the coordination reactions of dicarbonylic compounds with metallic nucleus of copper (II) and iron (III), for best of our knowledge, these compounds have not been described in the literature. The compounds were obtained in a shape of fine dust and identified per infra red spectroscopy.